A polypeptide inhibitor of calcineurin blocks the calcineurin-NFAT signalling pathway in vivo and in vitro. (1st January 2022) - Wang, Ping; Li, Wenying; Yang, Yumeng; Cheng, Na; Zhang, Yuchen; Zhang, Nan; Yin, Yanxia; Tong, Li; Li, Zhimei; Luo, Jing
Abstract: Calcineurin (CN) controls the immune response by regulating nuclear factor of activated T cells (NFAT). Inhibition of CN function is an effective treatment for immune diseases. The PVIVIT peptide is an artificial peptide based on the NFAT-PxIxIT motif, which exhibits stronger binding to CN. A bioactive peptide (named pep4) that inhibits the CN/NFAT interaction was designed. Pep4 contains a segment of A238L as the linker and the LxVP motif and PVIVIT motif as CN binding sites. Pep4 has strong binding capacity to CN and inhibits CN activity competitively. 11-arginine-modified pep4 (11 R-pep4) inhibits the nuclear translocation of NFAT and reduces the expression of IL-2. 11 R-pep4 improves the pathological characteristics of asthmatic mice to a certain extent. The above results indicated that pep4 is a high-affinity CN inhibitor. These findings will contribute to the discovery of new CN inhibitors and promising immunosuppressive drugs.